Cyber security essentials - Graham, James (James J.); Howard, Richard, 1959-; Olson, Ryan, 1981- (Boca Raton : Auerbach Publications, 2011)
'A collection of intelligence and security articles, this book covers common security terms and vulnerabilities that security and IT personnel need to know in order to guard their systems. Topics discussed include Stack Based Buffer Overflows, Malware Naming, Fast-Flux, SQL Injection, and Format String Vulnerability. The book explains more than 75 common security vulnerabilities clearly and concisely in short, well-illustrated, descriptions that are easy to read and comprehend. The author provides actionable advice on how to mitigate each vulnerability, helping to enable a proactive response to threats and attacks'--
Includes bibliographical references and index.
Keywords: Computer security